Empowering Elderly Voters with Special Health Conditions in Pemecutan Kaja Village: Socialization and Education to Prevent Voter Abstention - Adyatna Wedananta, Kadek; Raihandi, Rizki (Jurnal Karya Abdi Masyarakat, 2024)
Elections are an important moment for every citizen to participate in determining the direction of governance. However, voter participation, especially among the elderly, faces significant challenges. In Indonesia, the low voter turnout, partly due to the phenomenon of "golput in Bahasa" (abstain voters) or not exercising the right to vote, has become a serious concern. In several previous elections, there has been a noticeable decline in participation among the elderly, indicating a lack of understanding of their important role in the democratic process. The lack of socialization is one of the factors contributing to elderly voters not exercising their voting rights. Additionally, specific health conditions often experienced by the elderly add complexity to the issue of abstaining voters. As a vulnerable group, the elderly frequently face physical and mental challenges that hinder their participation in elections. To address this issue, a community service program themed "Socialization and Education on Preventing Abstain Voters for Elderly Voters with Special Health Conditions in Pemecutan Kaja Village" is expected to provide the necessary education to encourage the elderly to exercise their voting rights in elections.